Experimental Mycotoxicosis in Layer Induced by Ochratoxin A and its Amelioration with Herbomineral Toxin Binder ‘Toxiroak’ - Sawale, G.K.; Gosh, R.C.; Ravikanth, K.; Maini, S.; Rekhe, D.S. (International Journal of Poultry Science, 2009)
A study was conducted in 80 white leghorn 26 week old laying hen to evaluate toxic effects of ochratoxin A and preventive efficacy of herbomineral toxin binder product (Toxiroak®). Birds were randomly divided into four groups of 20 each. Group I served as control and given no treatment, Group II comprised healthy birds fed standard basal diet and administered Toxiroak@1.25 kg/tonne of feed for 60 days, birds of group III received ochratoxin A@1 ppm while those of group IV were given ochratoxin A@1 ppm and herbomineral toxin binder product Toxiroak@1.25 kg/tonne of feed for 60 days. Ochratoxin A adversely affects body weight gain, feed consumption, laying performance of hens besides haematobiochemical disturbances & severe immunosupression. However, supplementation of herbomineral toxin binder feed supplement has provided a moderate amelioration in mycotoxicosis.